ANALISIS KONTRIBUSI SEKTOR PERTANIAN MELALUI PENDEKATAN EFISIENSI SUB SEKTOR PERTANIAN DI KABUPATEN MELAWI - B01108040, Hendrawan Riskiyadi (Jurnal Pembangunan dan Pemerataan, 2013)
The agricultural sector is the dominant sector of each region so as to make a special attraction to be investigated more deeply. The purpose of this study analyzed the contribution of the agricultural sector is the approach in the agriculture sub-sector efficiency Melawi 2006-2011. The data obtained will be analyzed using analysis tools DEA (Data Envelopment Analysis). This study uses a descriptive method is explorative. Data collection statistics obtained through the central body of West Kalimantan and central body Melawi statistics. The results showed that, five agricultural sector has reached a whole reached a value of 100 percent is very good to be developed. There are years that has not reached the value of 100 per cent in every agricultural sector shows that the agricultural sector is not efficient. To achieve the efficient, we need to hold reductions or additions to the input and output of the agricultural sector. Keywords: Agricultural Sector Contribution Analysis Approach Through Efficiency in Agriculture Sector Sub Melawi.